1998
DOI: 10.1152/jappl.1998.84.6.1895
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia in endurance-trained people during a short interruption to training

Abstract: This study examined changes in postprandial lipemia in endurance-trained people during a short interruption to training. Nine men and one woman (ages 18-55 yr) undertook fat tolerance tests after 15 h, 60 h, and 6.5 days without exercise. The test meal (1.2 g fat, 1.1 g carbohydrate, 66 kJ/kg body mass) was consumed after a 12-h fast. Postprandial lipemia increased rapidly with detraining (area under plasma triacylglycerol vs. time curve: 8.42 +/- 1.40, 11. 35 +/- 1.38, and 11.97 mM x 6 h at 15 h, 60 h and 6.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 33 publications
6
70
1
5
Order By: Relevance
“…This is in agreement with the majority of the studies that have compared this outcome measure or an equivalent one, time-averaged concentration, after a high-fat meal consumed 12-18 h following aerobic exercise vs rest (Tsetsonis & Hardman, 1996a (moderate intensity trial), 1996b; Tsetsonis et al, 1997;Hardman et al, 1998;Gill et al, 1998Gill et al, , 2001aGill et al, , b, 2003Malkova et al, 1999Malkova et al, , 2000Gill & Hardman, 2000;Herd et al, 2001;. Three studies have found no significant difference between exercise and rest (Tsetsonis & Hardman, 1996a (low-intensity trial); Herd et al, 1998;Petitt et al, 2003).…”
Section: Exercise and Lipemia After A Moderate Fat Meal M Kolifa Et Alsupporting
confidence: 82%
See 3 more Smart Citations
“…This is in agreement with the majority of the studies that have compared this outcome measure or an equivalent one, time-averaged concentration, after a high-fat meal consumed 12-18 h following aerobic exercise vs rest (Tsetsonis & Hardman, 1996a (moderate intensity trial), 1996b; Tsetsonis et al, 1997;Hardman et al, 1998;Gill et al, 1998Gill et al, , 2001aGill et al, , b, 2003Malkova et al, 1999Malkova et al, , 2000Gill & Hardman, 2000;Herd et al, 2001;. Three studies have found no significant difference between exercise and rest (Tsetsonis & Hardman, 1996a (low-intensity trial); Herd et al, 1998;Petitt et al, 2003).…”
Section: Exercise and Lipemia After A Moderate Fat Meal M Kolifa Et Alsupporting
confidence: 82%
“…In unison with all the relevant studies (Tsetsonis & Hardman, 1996a, b;Tsetsonis et al, 1997;Gill et al, 1998Gill et al, , 2001aHardman et al, 1998;Herd et al, 1998Herd et al, , 2001Malkova et al, 1999;Gill & Hardman, 2000;Malkova et al, 2000;Petitt et al, 2003), the postprandial glycemic response did not differ between exercise and control, confirming the strong homeostasis of plasma glucose. No difference was found in the insulinemic response either.…”
Section: Exercise and Lipemia After A Moderate Fat Meal M Kolifa Et Alsupporting
confidence: 71%
See 2 more Smart Citations
“…In endurance athletes, just 60 h without training resulted in an increase of more than one third in postprandial lipaemia, with a further (but much smaller) increase after a total of six days without training. 61 This ties in well with a rapid decrease in postheparin plasma LPL activity after only two days without training, in trained men and women. 62 On this evidence, the effects of a recent training session are probably subsumed within the measures of TAG capacity reported for endurance athletes in some studies.…”
Section: Exercise and Postprandial Lipid And Lipoprotein Metabolismsupporting
confidence: 54%